KAJIAN MOTIF “GARUDAMUKHA” BATIK SUMINAR - Ilham Rosyadi Hidayatulloh; Sarah Rum Handayani (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2022)
Kediri is one of the cities / regencies in East Java province that still produces textile production, namely batik. The problems discussed in this study are (1) what is the background of the creation of Garudamukha Batik in Kediri batik? (2) how to design Garudamukha Batik on Kediri batik using a design approach? This research uses descriptive qualitative research methods with the design approach and design theory from Nanang Rizali. Data obtained using passive role observation, in-depth interviews, and literature study. Focusing on the background of the formation of Garudamukha Batik and the symbolic meaning it contains. The research sites are in Kediri Regency and Kediri City, Badas District, Gurah District, Pagu District, Semen District, and Mojo District. The results showed that: 1) In the history of Batik Garudamukha was formed on the initiative of the City Government of Kediri. Garudamukha is one of the history in Kediri, the mount of Lord Vishnu. King Airlangga is trusted by his people as the incarnation of Lord Vishnu who has the territory in the City of Kediri namely DAHA or Dahapura (City of Fire). 2) The function aspect acts as the identity of the City of Kediri. Aesthetic aspects in the form of decoration, color, composition. The material aspect uses primissima cotton cloth, wax and remasol dyes. The aspect of the process uses written, stamped, printing or mixed techniques.